PERSEPSI MAHASISWA TERHADAP PELAKSANAAN METODE EXTENSIVE READING DALAM PEMBELAJARAN BAHASA JEPANG - Yoya Rahman; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study discusses students' perceptions of the implementation of the extensive reading method in learning Japanese language. The method used in this research is descriptive quantitative method. This research takes place at the Japanese Language Education Study Program, FKIP, Riau University. The source of data in this study is a questionnaire. The number of respondents in this study were students who took the tadoku 2 course, totaling 28 students. The data analysis technique used a Likert scale measurement. The results of the analysis of the data obtained in this study are in the implementation of the extensive reading method there are benefits and obstacles felt by students during learning. From the benefits obtained by students in implementing the extensive reading method, there are aspects of motivation, general knowledge, grammatical knowledge, and independence. Meanwhile, the obstacles experienced by students in implementing extensive reading are in terms of understanding, independence, and the environment.Key Words: Perception, Extensive Reading